PENINGKATAN PARTISIPASI PEMILIH DI MASA PANDEMI COVID-19 PADA PEMILIHAN BUPATI SIMALUNGUN TAHUN 2020 - Ginting, Delphy Embarina; Apriani, Kadek Dwita; Mertha, Anak Agung Sagung Mirah Mahaswari Jayanthi (Jurnal Nawala Politika; Vol 1 No 2 (2022): Jurnal Ilmu Politik, 2022)
This study aims to determine community participation during the Covid-19 pandemic in the 2020 Simalungun Regent election. The data obtained uses informant interviews that can provide accurate explanations and literature study techniques collect data in the form of data sources, references or documents that are important and relevant to the research. The results showed that there was an increase in community participation even during the Covid-19 pandemic due to various indicators, namely the political awareness of the people of Simalungun regency aware of their rights and responsibilities so that the community was willing to participate in the election. Second, the strength of candidates, people tend to participate in elections because of the candidates they have won. Third, the socialization of the KPU as the organizer in the 2020 regent and deputy regent elections is an important factor because the implementation of the 2020 elections is different from previous years. Keyword:Participation, Local Elections, Pandemic,Simalungun district